Identification of Factors Affecting the Life Expectancy (LE) of Building in Malaysia - Mohd Subri, Syaza Aisyah; Abu Bakar, Anisah Sufiah; Razali, Nur Ain; Mohammad, Hairuddin (Multidisciplinary Applied Research and Innovation, 2024)
In Malaysia, building collapses are always a national concern. These collapses occur because some buildings have outlived their useful lives. Majority of homeowners and building owners have no idea what causes the collapse. As the concern engulfed the owners, this is is due to lack of understanding of the underlying cause. Therefore, a study on life expectancy is conducted to identify and validate the factors that might be influential to the building. To achieve this goal, this study used a mixed methodology; literature review with help of multi-layered thematic (MLT) document analysis and questionnaire survey to validate all factors influencing LE. The findings will be used by the government or the private sector to organize and develop building maintenance guidelines and standards. It will also help the homeowners and construction professionals conduct proactive maintenance perimeters and monitor the quality of their construction.